Segment-based packet combining: how to schedule a dense relayer cluster? - Willig, Andreas; Karl, Holger; Kipnis, Danil (Wireless Networks)

Average and competitive analysis of latency and power consumption of a queuing system with a sleep mode - Herlich, Matthias; Karl, Holger (Proceedings of the 3rd International Conference on Energy-Efficient Computing and Networking, e-Energy'12, Madrid, Spain, May 9-11, 2012)

Energy Efficient Clustering using a Wake-up Receiver - Blanckenstein, Johannes; Klaue, Jirka; Karl, Holger (European Wireless 2012 - 18th European Conference 2012, April 18-20, 2012, Poznan, Poland.)

On Local Separation of Processing and Storage in Infrastructure-as-a-Service - Künsemöller, Jörn; Karl, Holger (Economics of Grids, Clouds, Systems, and Services - 9th International Conference, GECON 2012, Berlin, Germany, November 27-28, 2012. Proceedings)

Efficiency of On-Path and Off-Path Caching Strategies in Information Centric Networks - Dräxler, Martin; Karl, Holger (2012 IEEE International Conference on Green Computing and Communications, Conference on Internet of Things, and Conference on Cyber, Physical and Social Computing, GreenCom/iThings/CPSCom 2012, Besancon, France, November 20-23, 2012)

OpenNetInf - prototyping an information-centric Network Architecture - Dannewitz, Christian; Herlich, Matthias; Karl, Holger (37th Annual IEEE Conference on Local Computer Networks, Workshop Proceedings, Clearwater Beach, FL, USA, October 22-25, 2012)

Cooperating base station set selection and network reconfiguration in limited backhaul networks - Dräxler, Martin; Biermann, Thorsten; Karl, Holger; Kellerer, Wolfgang (23rd IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2012, Sydney, Australia, September 9-12, 2012)

Using OMNeT++ for energy optimization simulations in mobile core networks - Dräxler, Martin; Beister, Frederic; Kruska, Stephan; Aelken, J.; Karl, Holger (International ICST Conference on Simulation Tools and Techniques, SIMUTOOLS '12, Sirmione-Desenzano, Italy, March 19-23, 2012)

Quantization techniques for accurate soft message combining - Volkhausen, Tobias; Schinköthe, Kai; Karl, Holger (2012 IEEE Wireless Communications and Networking Conference, WCNC 2012, Paris, France, April 1-4, 2012)

Efficient cooperative relaying in wireless multi-hop networks with commodity WiFi hardware - Volkhausen, Tobias; Dridger, Kornelius; S. Lichte, Hermann; Karl, Holger (10th International Symposium on Modeling and Optimization in Mobile, Ad Hoc and Wireless Networks (WiOpt), Paderborn, Germany, May 14-18, 2012)

Model-driven Performance Engineering of Self-Adaptive Systems: A Survey - Becker, Matthias; Luckey, Markus; Becker, Steffen (Proceedings of the International Conference on Quality of Software Architecture)

Towards an Automatic Service Discovery for UML-based Rich Service Descriptions - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the ACM/IEEE 15th International Conference on Model Driven Engineering Languages and Systems (MODELS'12))
Service-oriented computing (SOC) promises to solve many issues in the area of distributed software development, e.g. the realization of the loose coupling pattern in practice through service discovery and invocation. For this purpose, service descriptions must comprise structural as well as behavioral information of the services otherwise an accurate service discovery is not possible. We addressed this issue in our previous paper and proposed a UML-based rich service description language (RSDL) providing comprehensive notations to specify service requests and offers. However, the automatic matching of service requests and offers specified in a RSDL for the purpose of service discovery is a complex task, due to multifaceted heterogeneity of the service partners. This heterogeneity includes the use of different underlying ontologies or different levels of granularity in the specification itself resulting in complex mappings between service requests and offers. In this paper, we present an automatic matching mechanism for service requests and offers specified in a RSDL that overcomes the underlying heterogeneity of the service partners.

Quasar 3.0 - A Situational Approach to Software Engineering - Kremer, Marion; Engels, Gregor; Hofmann, Alexander; Hohwiller, Jörg; E. Nandico, Oliver; Nötzold, Thomas; Prott, Karl; Schlegel, Diethelm; Seidl, Andreas; Wolf, Thomas

Towards the Application of Reinforcement Learning Techniques for Quality-Based Service Selection in Automated Service Composition - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 9th IEEE International Conference on Service Computing (SCC))
A major goal of the On-The-Fly Computing project is the automated composition of individual services based on services that are available in dynamic markets. Dependent on the granularity of a market, different alternatives that satisfy the requested functional requirements may emerge. In order to select the best solution, services are usually selected with respect to their quality in terms of inherent non-functional properties. In this paper, we describe our idea of how to model this service selection process as a Markov Decision Process, which we in turn intend to solve by means of Reinforcement Learning techniques in order to control the underlying service composition process. In addition, some initial issues with respect to our approach are addressed.

Cloud Service Revenue Management - Püschel, Tim; Schryen, Guido; Hristova, Diana; Neumann, Dirk (European Conference on Information Systems)

Elicitating, modeling, and processing uncertain human preferences for software agents in electronic negotiations: An empirical study - Lang, Fabian; Schryen, Guido; Fink, Andreas (International Conference on Information Systems)

Energy-Aware Workload Management Models for Operating Cost Reduction in Data Centers - Bodenstein, Christian; Schryen, Guido; Neumann, Dirk (European Journal of Operational Research : EJOR)

Towards Modeling Reconfiguration in Hierarchical Component Architectures - Becker, Steffen; Heinzemann, Christian; Priesterjahn, Claudia (Proceedings of the 15th ACM SigSoft International Symposium on Component-Based Software Engineering (CBSE))
Today's real-time embedded systems operate in frequently changing environments on which they react by self-adaptations. Such an approach needs adequate modeling support of these reconfigurations to enable verification of safety properties, e.g., by timed model checking. Component-based development of such systems realizes these self-adaptations by structural reconfigurations of components and their connectors. However, component models proposed in literature do not support reconfigurable components in real-time embedded context but focus on other domains like business information systems. In this paper, we present an extension of our modeling language MechatronicUML to support structural reconfigurations taking the specific requirements of our domain into account. Based on the proposed extension we outline our research roadmap to achieve verification and realization of systems modeled in MechatronicUML.

Towards higher-dimensional topological self-stabilization: A distributed algorithm for Delaunay graphs - Jacob, Riko; Ritscher, Stephan; Scheideler, Christian; Schmid, Stefan (Theoretical Computer Science)
This article studies the construction of self-stabilizing topologies for distributed systems. While recent research has focused on chain topologies where nodes need to be linearized with respect to their identiers, we explore a natural and relevant 2-dimensional generalization. In particular, we present a local self-stabilizing algorithm DStab which is based on the concept of \local Delaunay graphs" and which forwards temporary edges in greedy fashion reminiscent of compass routing. DStab constructs a Delaunay graph from any initial connected topology and in a distributed manner in time O(n3) in the worst-case; if the initial network contains the Delaunay graph, the convergence time is only O(n) rounds. DStab also ensures that individual node joins and leaves aect a small part of the network only. Such self-stabilizing Delaunay networks have interesting applications and our construction gives insights into the necessary geometric reasoning that is required for higherdimensional linearization problems.Keywords: Distributed Algorithms, Topology Control, Social Networks

Towards an Integrated Service Rating and Ranking Methodology for Quality Based Service Selection in Automatic Service Composition - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 4th International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
The paradigm shift from purchasing monolithic software solutions to a dynamic composition of individual solutions entails many new possibilities yet great challenges, too. In order to satisfy user requirements, complex services have to be automatically composed of elementary services. Multiple possibilities of composing a complex service inevitably emerge. The problem of selecting the most appropriate services has to be solved by comparing the different service candidates with respect to their quality in terms of inherent non-functional properties while simultaneously taking the user requirements into account. We are aiming for an integrated service rating and ranking methodology in order to support the automation of the underlying decision-making process. The main contribution of this paper is a ﬁrst decomposition of the quality-based service selection process, while emphasizing major issues and challenges, which we are addressing in the On-The-Fly Computing project.

Perils of Managing the Service Profit Chain: The Role of Time Lags and Feedback Loops. - Evanschitzky, Heiner; Wangenheim, Florian v; Wünderlich, Nancy (Journal of Retailing)
The tendency of managers to focus on short-term results rather than on sustained company success is of particular importance to retail marketing managers, because marketing activities involve expenditures which may only pay off in the longer term. To address the issue of myopic management, our study shows how the complexity of the service profit chain (SPC) can cause managers to make suboptimal decisions. Hence, our paper departs from past research by recognizing that understanding the temporal interplay between operational investments, employee satisfaction, customer satisfaction, and operating profit is essential to achieving sustained success. In particular, we intend to improve understanding of the functioning of the SPC with respect to time lags and feedback loops. Results of our large-scale longitudinal study set in a multi-outlet retail chain reveal time-lag effects between operational investments and employee satisfaction, as well as between customer satisfaction and performance. These findings, along with evidence of a negative interaction effect of employee satisfaction on the relationship between current performance and future investments, show the substantial risk of mismanaging the SPC. We identify specific situations in which the dynamic approach leads to superior marketing investment decisions, when compared to the conventional static view of the SCP. These insights provide valuable managerial guidance for effectively managing the SPC over time.
Keywords: Employee satisfaction; Customer satisfaction; Performance; Service profit chain; Feedback loops; Time lags; Myopic marketing management

Culture’s Impact on Customer Motivation to Engage in Professional Service Enactments. - Schumann, Jan H; Wünderlich, Nancy; Zimmer, Marcus S (Schmalenbach Business Review)
Although professional service providers increasingly deliver their services globally, little is known about cross-cultural differences in customers’ motivation to participate in service production. To address this lacuna, we survey a total of 2,284 banking customers in 11 countries on their motivation to provide personal information to, and follow the advice of, their service providers. We find differences in both aspects, but only the differences in providing personal information can be explained by the cultural values of uncertainty avoidance, individualism/collectivism, and masculinity/femininity. To perform certain tasks in the service process, global professional service providers should acknowledge cultural differences in customers’ motivations.
Keywords: Co-Production; Culture; Customer Participation; Professional Services

Technology Mediation in Service Delivery: A New Typology and an Agenda for Managers and Academics. - Schumann, Jan H; Wünderlich, Nancy; Wangenheim, Florian (Technovation)
The role of information and communication technology for economic growth has been emphasized repeatedly. Technological breakthroughs have generated new forms of services, such as self-services or remote services. Although these encounters are qualitatively different from traditional service provision, prior service management literature thus far had paid little attention to theory development and the systematization of technology-based service encounters. To fill this research gap, the present study outlines how new types of technology-based services fit into existing service typologies and provides an extension of existing frameworks to capture their unique characteristics. These insights in turn offer managerial implications and highlight open research questions.
Keywords: Services; Remote services; Self-services; Technology mediation

Towards an Automatic Service Discovery for UML-based Rich Service Descriptions - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the ACM/IEEE 15th International Conference on Model Driven Engineering Languages and Systems (MoDELS))
Service-oriented computing (SOC) promises to solve many issues in the area of distributed software development, e.g. the realization of the loose coupling pattern in practice through service discovery and invocation. For this purpose, service descriptions must comprise structural as well as behavioral information of the services otherwise an accurate service discovery is not possible. We addressed this issue in our previous paper and proposed a UML-based rich service description language (RSDL) providing comprehensive notations to specify service requests and offers.However, the automatic matching of service requests and offers specified in a RSDL for the purpose of service discovery is a complex task, due to multifaceted heterogeneity of the service partners. This heterogeneity includes the use of different underlying ontologies or different levels of granularity in the specification itself resulting in complex mappings between service requests and offers. In this paper, we present an automatic matching mechanism for service requests and offers specified in a RSDL that overcomes the underlying heterogeneity of the service partners.

Towards a Framework for the Integration of Modeling Languages - Arifulina, Svetlana (Proceedings of the Doctoral Symposium of the 5th International Conference on Software Language Engineering 2012, Dresden, Germany (SLE (Doctoral Symposium)))
In software markets of the future, customer-specific software will be developed on demand from distributed software and hardware services available on world-wide markets. Having a request, services have to be automatically discovered and composed. For that purpose, services have to be matched based on their specifications. For the accurate matching, services have to be described comprehensively that requires the integration of different domain-specific languages (DSLs) used for functional, non-functional, and infrastructural properties. Since different service providers use plenty of language dialects to model the same service property, their integration is needed for the matching. In this paper, we propose a framework for integration of DSLs. It is based on a parameterized abstract core language that integrates key concepts needed to describe a service. Parts of the core language can be substituted with concrete DSLs. Thus, the framework serves as a basis for the comprehensive specification and automatic matching of services.

Tiara: A self-stabilizing deterministic skip list and skip graph - Clouser, Thomas; Nesterenko, Mikhail; Scheideler, Christian (Theoretical Computer Science)
We present Tiara — a self-stabilizing peer-to-peer network maintenance algorithm. Tiara is truly deterministic which allows it to achieve exact performance bounds. Tiara allows logarithmic searches and topology updates. It is based on a novel sparse 0-1 skip list. We then describe its extension to a ringed structure and to a skip-graph.Key words: Peer-to-peer networks, overlay networks, self-stabilization.

Symbiotic Coupling of Peer-to-Peer and Cloud Systems - Bremer, Lars

Model-driven specification of adaptive cloud-based systems - Nagel, Benjamin; Gerth, Christian; Yigitbas, Enes; Christ, Fabian; Engels, Gregor (Proceedings of the 1st International Workshop on Model-Driven Engineering for High Performance and CLoud computing co-located with 15th International Conference on Model Driven Engineering Languages and Systems {(MODELS} 2012), Innsbruck, Austria, October 01 - 05, 2012)

Stereo Matching on a Convey HC-1 Hybrid Core Computer - Schmitz, Henning

Entwicklung eines Monitoring- und Adaptionskonzeptes für Geschäftsprozesse in service-orientierten Systemen - Yigitbas, Enes

Stabilization, Safety, and Security of Distributed Systems
SSS is an international forum for researchers and practitioners in the design and development of distributed systems with self-properties: (classical) self-stabilizing, self-configuring, self-organizing, self-managing, self-repairing, self-healing, self-optimizing, self-adaptive, and self-protecting. Research in distributed systems is now at a crucialpoint in its evolution, marked by the importance of dynamic systems such as peer-to-peer networks, large-scale wireless sensor networks, mobile ad hoc networks, cloud computing, robotic networks, etc. Moreover, new applications such as grid and web services, banking and e-commerce, e-health and robotics, aerospace and avionics, automotive, industrial process control, etc. have joined the traditional applications of distributed systems. The theory of self-stabilization has been enriched in the last 30 years by high quality research contributions in the areas of algorithmic techniques, formal methodologies, model theoretic issues, and composition techniques. All these areas are essential to the understanding and maintenance of self-properties in fault-tolerant distributed systems.

Stability of Coalitional Equilibria within Repeated Tax Competition - Brangewitz, Sonja; Brockhoff, Sarah
This paper analyzes the stability of capital tax harmonization agreements in a stylized model where countries have formed coalitions which set a common tax rate in order to avoid the inefficient fully non-cooperative Nash equilibrium. In particular, for a given coalition structure we study to what extend the stability of tax agreements is affected by the coalitions that have formed. In our set-up, countries are symmetric, but coalitions can be of arbitrary size. We analyze stability by means of a repeated game setting employing simple trigger strategies and we allow a sub-coalition to deviate from the coalitional equilibrium. For a given form of punishment we are able to rank the stability of different coalition structures as long as the size of the largest coalition does not change. Our main results are: (1) singleton regions have the largest incentives to deviate, (2) the stability of cooperation depends on the degree of cooperative behavior ex-ante.

Smoothed analysis of left-to-right maxima with applications - Damerow, Valentina; Manthey, Bodo; Meyer auf der Heide, Friedhelm; Räcke, Harald; Scheideler, Christian; Sohler, Christian; Tantau, Till (Transactions on Algorithms)
A left-to-right maximum in a sequence of n numbers s_1, …, s_n is a number that is strictly larger than all preceding numbers. In this article we present a smoothed analysis of the number of left-to-right maxima in the presence of additive random noise. We show that for every sequence of n numbers s_i ∈ [0,1] that are perturbed by uniform noise from the interval [-ε,ε], the expected number of left-to-right maxima is Θ(&sqrt;n/ε + log n) for ε>1/n. For Gaussian noise with standard deviation σ we obtain a bound of O((log3/2 n)/σ + log n).We apply our results to the analysis of the smoothed height of binary search trees and the smoothed number of comparisons in the quicksort algorithm and prove bounds of Θ(&sqrt;n/ε + log n) and Θ(n/ε+1&sqrt;n/ε + n log n), respectively, for uniform random noise from the interval [-ε,ε]. Our results can also be applied to bound the smoothed number of points on a convex hull of points in the two-dimensional plane and to smoothed motion complexity, a concept we describe in this article. We bound how often one needs to update a data structure storing the smallest axis-aligned box enclosing a set of points moving in d-dimensional space.

Slow Down & Sleep for Profit in Online Deadline Scheduling - Cord-Landwehr, Andreas; Kling, Peter; Mallmann Trenn, Fredrik (Proceedings of the 1st Mediterranean Conference on Algorithms (MedAlg))
We present and study a new model for energy-aware and profit-oriented scheduling on a single processor.The processor features dynamic speed scaling as well as suspension to a sleep mode.Jobs arrive over time, are preemptable, and have different sizes, values, and deadlines.On the arrival of a new job, the scheduler may either accept or reject the job.Accepted jobs need a certain energy investment to be finished in time, while rejected jobs cause costs equal to their values.Here, power consumption at speed $s$ is given by $P(s)=s^{α}+β$ and the energy investment is power integrated over time.Additionally, the scheduler may decide to suspend the processor to a sleep mode in which no energy is consumed, though awaking entails fixed transition costs $γ$.The objective is to minimize the total value of rejected jobs plus the total energy.Our model combines aspects from advanced energy conservation techniques (namely speed scaling and sleep states) and profit-oriented scheduling models.We show that rejection-oblivious schedulers (whose rejection decisions are not based on former decisions) have – in contrast to the model without sleep states – an unbounded competitive ratio.It turns out that the jobs' value densities (the ratio between a job's value and its work) are crucial for the performance of such schedulers.We give an algorithm whose competitiveness nearly matches the lower bound w.r.t\text{.} the maximum value density.If the maximum value density is not too large, the competitiveness becomes $α^{α}+2eα$.Also, we show that it suffices to restrict the value density of low-value jobs only.Using a technique from \cite{Chan:2010} we transfer our results to processors with a fixed maximum speed.

Self-Organizing Particle Systems - Drees, Maximilian; Hüllmann (married name: Eikel), Martina; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 26th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
Nanoparticles are getting more and more in the focus of the scientic community since the potential for the development of very small particles interacting with each other and completing medical and other tasks is getting bigger year by year. In this work we introduce a distributed local algorithm for arranging a set of nanoparticles on the discrete plane into specic geometric shapes, for instance a rectangle. The concept of a particle we use can be seen as a simple mobile robot with the following restrictions: it can only view the state of robots it is physically connected to, is anonymous, has only a constant size memory, can only move by using other particles as an anchor point on which it pulls itself alongside, and it operates in Look-Compute-Move cycles. The main result of this work is the presentation of a random distributed local algorithm which transforms any given connected set of particles into a particular geometric shape. As an example we provide a version of this algorithm for forming a rectangle with an arbitrary predened aspect ratio. To the best of our knowledge this is the rst work that considers arrangement problems for these types of robots.

Self-Optimizing Binary Search Trees - A Game Theoretic Approach - Strothmann, Thim Frederik

Revenue-maximizing Order of Sale in Sequential Auctions - Drücker, Julian

Queuing Latency at Cooperative Base Stations - Hohenberger, Till

Proxy Re-Encryption in a Privacy-Preserving Cloud Computing DRM Scheme - Petrlic, Ronald (Proceedings of 4th International Symposium on Cyberspace Safety and Security (CSS))
In a cloud-computing scenario where users buy software from software providers and execute it at computing centers, a digital rights management (DRM) system has to be in place to check the software licenses during each software execution. However, the exposure of users to privacy invasion in the presence of DRM systems is problematic.We come up with a concept that unites software providers' and users' demands for a secure and privacy-preserving DRM system for cloud computing. The employment of proxy re-encryption allows for a prevention of profile building (under pseudonym) of users by any party.

Proof-Carrying Hardware: A Novel Approach to Reconfigurable Hardware Security - Drzevitzky, Stephanie
FPGAs, systems on chip and embedded systems are nowadays irreplaceable. They combine the computational power of application specific hardware with software-like flexibility. At runtime, they can adjust their functionality by downloading new hardware modules and integrating their functionality. Due to their growing capabilities, the demands made to reconfigurable hardware grow. Their deployment in increasingly security critical scenarios requires new ways of enforcing security since a failure in security has severe consequences. Aside from financial losses, a loss of human life and risks to national security are possible. With this work I present the novel and groundbreaking concept of proof-carrying hardware. It is a method for the verification of properties of hardware modules to guarantee security for a target platform at runtime. The producer of a hardware module delivers based on the consumer's safety policy a safety proof in combination with the reconfiguration bitstream. The extensive computation of a proof is a contrast to the comparatively undemanding checking of the proof. I present a prototype based on open-source tools and an abstract FPGA architecture and bitstream format. The proof of the usability of proof-carrying hardware provides the evaluation of the prototype with the exemplary application of securing combinational and bounded sequential equivalence of reference monitor modules for memory safety.

Programming models for reconfigurable heterogeneous multi-cores - Plessl, Christian; Platzner, Marco; Agne, Andreas; Happe, Markus; Lübbers, Enno

Privacy-Preserving DRM for Cloud Computing - Petrlic, Ronald; Sorge, Christoph (Proceedings of the 26th IEEE International Conference on Advanced Information Networking and Applications (AINA))
We come up with a digital rights management (DRM) concept for cloud computing and show how license management for software within the cloud can be achieved in a privacy-friendly manner. In our scenario, users who buy software from software providers stay anonymous. At the same time, our approach guarantees that software licenses are bound to users and their validity is checked before execution. We employ a software re-encryption scheme so that computing centers which execute users’ software are not able to build user profiles—not even under pseudonym—of their users. We combine secret sharing and homomorphic encryption. We make sure that malicious users are unable to relay software to others. DRM constitutes an incentive for software providers to take part in a future cloud computing scenario.We make this scenario more attractive for users by preserving their privacy.

Privacy-Preserving Digital Rights Management in a Trusted Cloud Environment - Petrlic, Ronald (Proceedings of the 11th IEEE International Conference on Trust, Security and Privacy in Computing and Communications (TrustCom))
We present a privacy-preserving DRM scheme for a (future) cloud computing software market. In such a market, applications are packed into virtual machines (VMs) by software providers and the VMs can be executed at any computing center within the cloud. We propose the introduction of a software TPM as a container for VM-specific keys within the VM that moves around with the VM within the cloud. The software TPM is coupled to a virtual TPM at a computing center to constitute the root of trust for a local DRM enforcement system within the VM that checks the license before each application execution. This allows flexible price models, e.g. execute at most n timeslike models. Users have proof that their personally identifiable information, stored and processed within the VM at a computing center, cannot be obtained by the computing center. A feature of our solution is that neither software provider nor computing center are able to build usage profiles of the software executions.

Predicate Analysis with Block-Abstraction Memoization - Wonisch, Daniel; Wehrheim, Heike (Proceedings of the 14th International Conference on Formal Engineering Methods (ICFEM))
Predicate abstraction is an established technique for reducing the size of the state space during verification. In this paper, we extend predication abstraction with block-abstraction memoization (BAM), which exploits the fact that blocks are often executed several times in a program. The verification can thus benefit from caching the values of previous block analyses and reusing them upon next entry into a block. In addition to function bodies, BAM also performs well for nested loops. To further increase effectiveness, block memoization has been integrated with lazy abstraction adopting a lazy strategy for cache refinement. Together, this achieves significant performance increases: our tool (an implementation within the configurable program analysis framework CPAchecker) has won the Competition on Software Verification 2012 in the category “Overall”.

Penny Auctions: Design und Strategisches Verhalten - Celik, Aydin

Optimale Zuteilung von Nutzern zu verteilten Cloud-Standorten - Rojahn, Tobias

Online Parameteroptimierung in P2P-Netzwerken mit Hilfe von Neuronalen Netzen - Klerx, Timo

On scheduling with multi-core and multi-speed processors using power down - Mallmann Trenn, Frederik

Model-Driven Performance Engineering of Self-Adaptive Systems: A Survey - Becker, Matthias; Luckey, Markus; Becker, Steffen (Proceedings of the 8th ACM SigSoft International Conference on Quality of Software Architectures (QoSA'12))
To meet quality-of-service requirements in changing environments, modern software systems adapt themselves. The structure, and correspondingly the behavior, of these systems undergoes continuous change. Model-driven performance engineering, however, assumes static system structures, behavior, and deployment. Hence, self-adaptive systems pose new challenges to model-driven performance engineering. There are a few surveys on self-adaptive systems, performance engineering, and the combination of both in the literature. In contrast to existing work, here we focus on model-driven performance analysis approaches. Based on a systematic literature review, we present a classication, identify open issues, and outline further research.

Minimizing Expectation Plus Variance - Mavronicolas, Marios; Monien, Burkhard (Proceedings of the 5th International Symposium on Algorithmic Game Theory (SAGT))
We consider strategic games in which each player seeks a mixed strategy to minimize her cost evaluated by a concave valuation V (mapping probability distributions to reals); such valuations are used to model risk. In contrast to games with expectation-optimizer players where mixed equilibria always exist [15, 16], a mixed equilibrium for such games, called a V -equilibrium, may fail to exist, even though pure equilibria (if any) transfer over. What is the impact of such valuations on the existence, structure and complexity of mixed equilibria? We address this fundamental question for a particular concave valuation: expectation plus variance, denoted as RA, which stands for risk-averse; so, variance enters as a measure of risk and it is used as an additive adjustment to expectation. We obtain the following results about RA-equilibria:- A collection of general structural properties of RA-equilibria connecting to (i) E-equilibria and Var-equilibria, which correspond to the expectation and variance valuations E and Var, respectively, and to (ii) other weaker or incomparable equilibrium properties.- A second collection of (i) existence, (ii) equivalence and separation (with respect to E-equilibria), and (iii) characterization results for RA-equilibria in the new class of player-specific scheduling games. Using examples, we provide the first demonstration that going from E to RA may as well create new mixed (RA-)equilibria.- A purification technique to transform a player-specific scheduling game on identical links into a player-specific scheduling game so that all non-pure RA-equilibria are eliminated while new pure equilibria cannot be created; so, a particular game on two identical links yields one with no RA-equilibrium. As a by-product, the first-completeness result for the computation of RA-equilibria follows.

Methoden zur Bestimmung von innerbetrieblichen Verrechnungspreisen - Mammadov, Fuad

Managerial Delegation and Capacity Choices: An Analysis of the Cournot-Nash Equilibrium - Löwen, Xenia

Lokale Swaps und überholte Informationen in Basic Network Creation Games - Feldkord, Björn

Local strategies for robot formation problems - Kempkes, Barbara
Wir betrachten eine Gruppe von mobilen, autonomen Robotern in einem ebenen Gelände. Es gibt keine zentrale Steuerung und die Roboter müssen sich selbst koordinieren. Zentrale Herausforderung dabei ist, dass jeder Roboter nur seine unmittelbare Nachbarschaft sieht und auch nur mit Robotern in seiner unmittelbaren Nachbarschaft kommunizieren kann. Daraus ergeben sich viele algorithmische Fragestellungen. In dieser Arbeit wird untersucht, unter welchen Voraussetzungen die Roboter sich auf einem Punkt versammeln bzw. eine Linie zwischen zwei festen Stationen bilden können. Dafür werden mehrere Roboter-Strategien in verschiedenen Bewegungsmodellen vorgestellt. Diese Strategien werden auf ihre Effizienz hin untersucht. Es werden obere und untere Schranken für die benötigte Anzahl Runden und die Bewegungsdistanz gezeigt. In einigen Fällen wird außerdem die benötigte Bewegungsdistanz mit derjenigen Bewegungsdistanz verglichen, die eine optimale globale Strategie auf der gleichen Instanz benötigen würde. So werden kompetititve Faktoren hergeleitet.

Learning by Trading in Infinite Horizon Strategic Market Games with Default - Brangewitz, Sonja
We study the consequences of dropping the perfect competition assumption in a standard infinite horizon model with infinitely-lived traders and real collateralized assets, together with one additional ingredient: information among players is asymmetric and monitoring is incomplete. The key insight is that trading assets is not only a way to hedge oneself against uncertainty and to smooth consumption across time: It also enables learning information. Conversely, defaulting now becomes strategic: Certain players may manipulate prices so as to provoke a default in order to prevent their opponents from learning. We focus on learning equilibria, at the end of which no player has incorrect beliefs — not because those players with heterogeneous beliefs were eliminated from the market (although default is possible at equilibrium) but because they have taken time to update their prior belief. We prove a partial Folk theorem à la Wiseman (2011) of the following form: For any function that maps each state of the world to a sequence of feasible and strongly individually rational allocations, and for any degree of precision, there is a perfect Bayesian equilibrium in which patient players learn the realized state with this degree of precision and achieve a payoff close to the one specified for each state.

Introducing feedback to preemptive routing and wavelength assignment algorithms for dynamic traffic scenarios - Wette, Philip; Karl, Holger
Preemptive Routing and Wavelength Assignment (RWA) algorithms preempt established lightpaths in case not enough resources are available to setup a new lightpath in a Wavelength Division Multiplexing (WDM) network. The selection of lightpaths to be preempted relies on internal decisions of the RWA algorithm. Thus, if dedicated properties of the network topology are required by the applications running on the network, these requirements have to be known by the RWA algorithm. Otherwise it might happen that by preempting a particular lightpath these requirements are violated. If, however, these requirements include parameters only known at the nodes running the application, the RWA algorithm cannot evaluate the requirements. For this reason a RWA algorithm is needed which involves its users in the preemption decisions. We present a family of preemptive RWA algorithms for WDM networks. These algorithms have two distinguishing features: a) they can handle dynamic trafﬁc by on-the-ﬂy reconﬁguration, and b) users can give feedback for reconﬁguration decisions and thus inﬂuence the preemption decision of the RWA algorithm, leading to networks which adapt directly to application needs. This is different from trafﬁc engineering where the network is (slowly) adapted to observed trafﬁc patterns. Our algorithms handle various WDM network conﬁgurations including networks consisting of heterogeneous WDM hardware. To this end, we are using the layered graph approach together with a newly developed graph model that is used to determine conﬂicting lightpaths.

Implementierung eines Branch-and-Bound-Algorithmus für nichtkonvexe gemischt-ganzzahlige Optimierungsprobleme mit quadratischen Nebenbedingungen - Seier, Henrik

Implementierung eines adaptiven Verfahrens zur Linearisierung von nicht-konvexen, nichtlinearen Wassernetzmodellen mit Hilfe einer Fehlerabschätzung - Isenberg, Florian

Assessing cognitive alignment in different types of dialog by means of a network model - Mehler, Alexander; Lücking, Andy; Menke, Peter (Neural Networks)

Evaluation of Technical Communication - Menke, Peter (Handbook of Technical Communication)

Identitätsbasierte Signaturen - Ein Sicherheitsbeweis für Signaturen auf Grundlage von Gap-Diffie-Hellman-Gruppen mit Hilfe des Forking-Lemmas - Löken, Nils

Identitätsbasierte Kryptographie - Implementierung von Paarungen für Körper der Charakteristik 2 - Haarhoff, Thomas

Heuristic-Guided Abstraction Refinement for Concurrent Systems - Timm, Nils; Wehrheim, Heike; Czech, Mike (Proceedings of the 14th International Conference on Formal Engineering Methods (ICFEM))
Predicate abstraction is an established technique in software verification. It inherently includes an abstraction refinement loop successively adding predicates until the right level of abstraction is found. For concurrent systems, predicate abstraction can be combined with spotlight abstraction, further reducing the state space by abstracting away certain processes. Refinement then has to decide whether to add a new predicate or a new process. Selecting the right predicates and processes is a crucial task: The positive effect of abstraction may be compromised by unfavourable refinement decisions. Here we present a heuristic approach to abstraction refinement. The basis for a decision is a set of refinement candidates, derived by multiple counterexample-generation. Candidates are evaluated with respect to their influence on other components in the system. Experimental results show that our technique can significantly speed up verification as compared to a naive abstraction refinement.

Generating Prototypes of Adaptive Component-based Software Systems for Performance Analysis - Mohr, Mario

Das Cranet-Projekt: Kreuzkulturelle Vergleiche im HR-Management. - Steinmetz, Holger; Schwens, C; Wehner, M; Kabst, Rüdiger (PERSONALquartely)

Editorial: Employer Branding: Strategie, Instrumente, Umsetzung - Kabst, Rüdiger; Baum, M (PERSONALquartely)

Generating Adjustable Temperature Gradients on modern FPGAs - Hangmann, Hendrik

Erweiterung von d3fact um die Domäne Wasserversorgung in Verbindung mit der Analyse und Implementierung eines hydraulischen Simulationsverfahrens - Wohlfarth, Stefan

Einführung in die Betriebswirtschaftslehre - Weber, W; Kabst, Rüdiger

Empirischer, quantitativer Vergleich von Modelltransformationssprachen - Lehrig, Sebastian

Determinants of Different Types of Born Globals. - Baum, M; Schwens, C; Kabst, R (Handbook of Research on Born Globals)

Die Messung von Joint-Venture Erfolg - Isidor, R; Schwens, C; Kabst, R (Markteintrittsstrategien - Dynamik und Komplexität)

Effiziente Paketbildung in mehrdimensionalen Verhandlungsproblemen - Kluczniok, Sven

Efficient Color-Based Image Segmentation and Feature Classification for Image Processing in Embedded Systems - Jungmann, Alexander; Kleinjohann, Bernd; Kleinjohann, Elisabeth; Bieshaar, Maarten (Proceedings of the Fourth International Conference on Resource Intensive Applications and Services (INTENSIVE))
In this paper, a color based feature extraction and classification approach for image processing in embedded systems in presented. The algorithms and data structures developed for this approach pay particular attention to reduce memory consumption and computation power of the entire image processing, since embedded systems usually impose strong restrictions regarding those resources. The feature extraction is realized in terms of an image segmentation algorithm. The criteria of homogeneity for merging pixels and regions is provided by the color classification mechanism, which incorporates appropriate methods for defining, representing and accessing subspaces in the working color space. By doing so, pixels and regions with color values that belong to the same color class can be merged. Furthermore, pixels with redundant color values that do not belong to any pre-defined color class can be completely discarded in order to minimize computational effort. Subsequently, the extracted regions are converted to a more convenient feature representation in terms of statistical moments up to and including second order. For evaluation, the whole image processing approach is applied to a mobile representative of embedded systems within the scope of a simple real-world scenario.

Distributed Sampling of Regular Graphs - Kurras, Sven

Distributed Computing in Fault-Prone Dynamic Networks - Brandes, Philipp; Meyer auf der Heide, Friedhelm (Proceedings of the 4th Workshop on Theoretical Aspects of Dynamic Distributed Systems (TADDS))
Dynamics in networks is caused by a variety of reasons, like nodes moving in 2D (or 3D) in multihop cellphone networks, joins and leaves in peer-to-peer networks, evolution in social networks, and many others. In order to understand such kinds of dynamics, and to design distributed algorithms that behave well under dynamics, many ways to model dynamics are introduced and analyzed w.r.t. correctness and eciency of distributed algorithms. In [16], Kuhn, Lynch, and Oshman have introduced a very general, worst case type model of dynamics: The edge set of the network may change arbitrarily from step to step, the only restriction is that it is connected at all times and the set of nodes does not change. An extended model demands that a xed connected subnetwork is maintained over each time interval of length T (T-interval dynamics). They have presented, among others, algorithms for counting the number of nodes under such general models of dynamics.In this paper, we generalize their models and algorithms by adding random edge faults, i.e., we consider fault-prone dynamic networks: We assume that an edge currently existing may fail to transmit data with some probability p. We rst observe that strong counting, i.e., each node knows the correct count and stops, is not possible in a model with random edge faults. Our main two positive results are feasibility and runtime bounds for weak counting, i.e., stopping is no longer required (but still a correct count in each node), and for strong counting with an upper bound, i.e., an upper bound N on n is known to all nodes.

Datenschutzgerechtes DRM im Cloud Computing - Mittendorf, Robert

Datenschutzgerechte E-Payment-Schemata im On-The-Fly Computing - Sekula, Stephan

Coverage Criteria for Testing DMM Specifications - Arifulina, Svetlana; Engels, Gregor; Soltenborn, Christian (Proceedings of the 11th International Workshop on Graph Transformation and Visual Modeling Techniques (GT-VMT))
Behavioral modeling languages are most useful if their behavior is specified formally such that it can e.g. be analyzed and executed automatically. Obviously, the quality of such behavior specifications is crucial. The rule-based semantics specification technique Dynamic Meta Modeling (DMM) honors this by using the approach of Test-driven Semantics Specification (TDSS), which makes sure that the specification at hand at least describes the correct behavior for a suite of test models. However, in its current state TDSS does not provide any means to measure the quality of such a test suite. In this paper, we describe how we have applied the idea of test coverage to TDSS. Similar to common approaches of defining test coverage criteria, we describe a data structure called invocation graph containing possible orders of applications ofDMM rules. Then we define different coverage criteria based on that data structure, taking the rule applications caused by the test suite’s models into account. Our implementation of the described approach gives the language engineer using DMM a means to reason about the quality of the language’s test suite, and also provides hints on how to improve that quality by adding dedicated test models to the test suite.

Competitive and fair throughput for co-existing networks under adversarial interference - Richa, Andrea W.; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 31st Annual ACM SIGACT-SIGOPS Symposium on Principles and Distributed Computing (PODC))
This paper initiates the formal study of a fundamental problem: How to efficiently allocate a shared communication medium among a set of K co-existing networks in the presence of arbitrary external interference? While most literature on medium access focuses on how to share a medium among nodes, these approaches are often either not directly applicable to co-existing networks as they would violate the independence requirement, or they yield a low throughput if applied to multiple networks. We present the randomized medium access (MAC) protocol COMAC which guarantees that a given communication channel is shared fairly among competing and independent networks, and that the available bandwidth is used efficiently. These performance guarantees hold in the presence of arbitrary external interference or even under adversarial jamming. Concretely, we show that the co-existing networks can use a Ω(ε2 min{ε, 1/poly(K)})-fraction of the non-jammed time steps for successful message transmissions, where ε is the (arbitrarily distributed) fraction of time which is not jammed.

Change and Validity Analysis in Deductive Program Verification - Jakobs, Marie-Christine

Brief Announcement: SplayNets - Towards Self-Adjusting Distributed Data Structures - Schmid, Stefan; Avin, Chen; Scheideler, Christian; Häupler, Bernhard; Lotker, Zvi (Proceedings of the 26th International Symposium on Distributed Computing (DISC))
This paper initiates the study of self-adjusting distributed data structures for networks. In particular, we present SplayNets: a binary search tree based network that is self-adjusting to routing request.We derive entropy bounds on the amortized routing cost and show that our splaying algorithm has some interesting properties.

Multi-Modal, Multi-Touch Interaction with Maps in Disaster Management Applications - Paelke, Volker; Nebe, Karsten; Geiger, Christian; Klompmaker, Florian; Fischer, Holger Gerhard (ISPRS - International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)

Brief Announcement: Hashed Predecessor Patricia Trie - A Data Structure for Efficient Predecessor Queries in Peer-to-Peer Systems - Kniesburges, Sebastian; Scheideler, Christian (Proceedings of the 26th International Symposium on Distributed Computing (DISC))
The design of ecient search structures for peer-to-peer systems has attracted a lot of attention in recent years. In this announcement we address the problem of nding the predecessor in a key set and present an ecient data structure called hashed Predecessor Patricia trie. Our hashed Predecessor Patricia trie supports PredecessorSearch(x) and Insert(x) and Delete(x) in O(log log u) hash table accesses when u is the size of the universe of the keys. That is the costs only depend on u and not the size of the data structure. One feature of our approach is that it only uses the lookup interface of the hash table and therefore hash table accesses may be realized by any distributed hash table (DHT).

Block Abstraction Memoization for CPAchecker - Wonisch, Daniel (Proceedings of the 18th International Conference on Tools and Algorithms for the Construction and Analysis of Systems (TACAS))
Block Abstraction Memoization (ABM) is a technique in software model checking that exploits the modularity of programs during verification by caching. To this end, ABM records the results of block analyses and reuses them if possible when revisiting the same block again. In this paper we present an implementation of ABM into the predicate-analysis component of the software-verification framework CPAchecker. With our participation at the Competition on Software Verification we aim at providing evidence that ABM can not only substantially increase the efficiency of predicate analysis but also enables verification of a wider range of programs.

Diversität, Konflikte und Leistung in Teams: Ein meta-analytisches Strukturgleichungsmodell - Schneid, M; Steinmetz, Holger; Isidor, R; Kabst, Rüdiger

Endogeneity in the behavioral sciences: An illustration with real data - Kabst, Rüdiger

Basic Network Creation Games with Communication Interests - Cord-Landwehr, Andreas; Huellmann (married name: Eikel), Martina; Kling, Peter; Setzer, Alexander (Proceedings of the 5th International Symposium on Algorithmic Game Theory (SAGT))
Network creation games model the creation and usage costs of networks formed by a set of selfish peers.Each peer has the ability to change the network in a limited way, e.g., by creating or deleting incident links.In doing so, a peer can reduce its individual communication cost.Typically, these costs are modeled by the maximum or average distance in the network.We introduce a generalized version of the basic network creation game (BNCG).In the BNCG (by Alon et al., SPAA 2010), each peer may replace one of its incident links by a link to an arbitrary peer.This is done in a selfish way in order to minimize either the maximum or average distance to all other peers.That is, each peer works towards a network structure that allows himself to communicate efficiently with all other peers.However, participants of large networks are seldom interested in all peers.Rather, they want to communicate efficiently with a small subset only.Our model incorporates these (communication) interests explicitly.Given peers with interests and a communication network forming a tree, we prove several results on the structure and quality of equilibria in our model.We focus on the MAX-version, i.e., each node tries to minimize the maximum distance to nodes it is interested in, and give an upper bound of O(\sqrt(n)) for the private costs in an equilibrium of n peers.Moreover, we give an equilibrium for a circular interest graph where a node has private cost Omega(\sqrt(n)), showing that our bound is tight.This example can be extended such that we get a tight bound of Theta(\sqrt(n)) for the price of anarchy.For the case of general networks we show the price of anarchy to be Theta(n).Additionally, we prove an interesting connection between a maximum independent set in the interest graph and the private costs of the peers.

Recruitment Process Outsourcing and Applicant Reactions: Does Image Make a Difference? - Wehner, M C; Giardini, A; Kabst, Rüdiger

Designing Multi-Modal Map-Based Interfaces for Disaster Management - Paelke, Volker; Nebe, Karsten; Geiger, Christian; Klompmaker, Florian; Fischer, Holger Gerhard (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI))

Authenticated Tangible Interaction using RFID and Depth-Sensing Cameras - Supporting Collaboration on Interactive Tabletops - Klompmaker, Florian; Fischer, Holger Gerhard; Jung, Helge (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI))

Integrating usability engineering in the software development lifecycle based on international standards - Fischer, Holger Gerhard (Proceedings of the 4th ACM SIGCHI symposium on Engineering interactive computing systems - EICS '12)

Attribute-basierte Verschlüsselung - Schleiter, Patrick

Enriching Disaster Control Management based on Human-Computer Design - Fischer, Holger Gerhard; Klompmaker, Florian (Proceedings of the 9th International Conference on Information Systems for Crisis Response and Management (ISCRAM))

Der Qualitätsstandard für Usability Engineering der German UPA – Aktueller Stand der Arbeiten - Fischer, Holger Gerhard; Geis, Thomas; Kluge, Oliver; Bogner, Christian; Polkehn, Knut (Jahresband Usability Professionals)

Archimetrix: Improved Software Architecture Recovery in the Presence of Design Deficiencies - Platenius, Marie Christin; von Detten, Markus; Becker, Steffen (Proceedings of the 16th European Conference on Software Maintenance and Reengineering (CSMR))
Maintaining software systems requires up-to-date models of these systems to systematically plan, analyse and execute the necessary reengineering steps. Often, no or only outdated models of such systems exist. Thus, a reverse engineering step is needed that recovers the system’s components, subsystems and connectors. However, reverse engineering methods are severely impacted by design deficiencies in the system’s code base, e.g., they lead to wrong component structures. Several approaches exist today for the reverse engineering of component-based systems, however, none of them explicitly integrates a systematic design deficiency removal into the process to improve the quality of the reverse engineered architecture. Therefore, in our Archimetrix approach, we propose to regard the most relevant deficiencies with respect to the reverse engineered component-based architecture and support reengineers by presenting the architectural consequences of removing a given deficiency. We validate our approach on the Common Component Modeling Example and show that we are able to identify relevant deficiencies and that their removal leads to an improved reengineered architecture.

Archimetrix: A Tool for Deficiency-Aware Software Architecture Reconstruction - von Detten, Markus (Proceedings of the 19th Working Conference on Reverse Engineering (WCRE))
Maintaining software systems requires up-to-date models of these systems to systematically plan, analyze, and execute the necessary reengineering steps. Often, no or only outdated models of such systems exist.Thus, a reverse engineering step is needed that recovers the system's components, subsystems, and connectors. However, reverse engineering methods are severely impacted by design deficiencies in the system's code base, e.g., they lead to wrong component structures.Therefore, Archimetrix enables the reengineer to detect the most relevant deficiencies with respect to a reverseengineered component-based architecture and supports him by presenting the architectural consequences of removinga given deficiency.

German UPA Qualitätsstandard für Usability Engineering - Behrenbruch, Kay; Bogner, Christian; Fischer, Holger Gerhard; Geis, Thomas; Geitner, Claudia; Heimgärtner, Rüdiger; Hofmann, Britta; Hunkirchen, Peter; Kluge, Oliver; Litzenberg, Britta; Molich, Rolf; Polkehn, Knut; et al.

Approximate Duality of Multicommodity Multiroute Flows and Cuts: Single Source Case - Kolman, Petr; Scheideler, Christian (Proceedings of the 23th ACM SIAM Symposium on Discrete Algorithms (SODA))
Given an integer h, a graph G = (V;E) with arbitrary positive edge capacities and k pairs of vertices (s1; t1); (s2; t2); : : : ; (sk; tk), called terminals, an h-route cut is a set F µ E of edges such that after the removal of the edges in F no pair si ¡ ti is connected by h edge-disjoint paths (i.e., the connectivity of every si ¡ ti pair is at most h ¡ 1 in (V;E n F)). The h-route cut is a natural generalization of the classical cut problem for multicommodity °ows (take h = 1). The main result of this paper is an O(h722h log2 k)-approximation algorithm for the minimum h-route cut problem in the case that s1 = s2 = ¢ ¢ ¢ = sk, called the single source case. As a corollary of it we obtain an approximate duality theorem for multiroute multicom-modity °ows and cuts with a single source. This partially answers an open question posted in several previous papers dealing with cuts for multicommodity multiroute problems.

Analyse, Konzeption und Implementierung von Aggregationsverfahren für Trinkwasserversorgungsnetze - Pischel, Daniel